Effect of exercises using Sensball to develop some physical and skill abilities of football players aged 10-13 years - Dilawar Anwar Mohammed, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The current study aims to develop exercises using Sensball technique to enhance physical and skill abilities of football players aged 10-13 years. It also seeks to determine values ​​of pre- and post-tests, identify impact of Sensball exercises to develop of certain physical and skill abilities in experimental group, and identify any differences in physical and skill abilities between two groups in post-tests. The study problem stems from fact that most youth training relies on traditional methods for developing players' physical and skill variables, neglecting newer methods and approaches. The researcher employed an experimental method using a randomized equivalent groups design with pre- and post-tests for both experimental and control groups, as this approach was deemed most suitable for the research problem. The research population consisted of football players aged 10-13 years, while the research sample comprised 26 young players from the Kiwan Sports Club football team. Twenty of these players were then randomly selected by lottery. The study results showed that training method used did not produce a clear and significant improvement in physical and skill abilities of young football players in control group. However, Sensball exercises positively impacted development of physical and skill abilities in post-tests and across all skills studied. Sensball exercises demonstrated a superior effect on physical and skill development in post-tests for both groups, with experimental group showing most significant improvement in both physical and skill abilities. The researcher recommends utilizing exercises developed to create similar programs for developing specific physical and skill abilities in football players aged 10-13, and applying research findings by incorporating Sensball exercises into training of football players aged 10-13.